Confinement effects in the step-growth polymerization within AAO templates and modeling. (28th March 2018) - Sanz, Belén; Ballard, Nicholas; Marcos-Fernández, Ángel; Asua, José M.; Mijangos, Carmen
Abstract: Nanostructured polyurethanes have attracted substantial interest for the generation of "smart" surfaces, but step-growth polymerization at the nanoscale has scarcely been reported. In this work, the synthesis of polyurethanes by step-growth polymerization in the nanocavities of anodized aluminum oxide (AAO) templates is studied, finding that the kinetics of the reaction was faster than in bulk, while the molecular weight and the dispersity were reduced. A mathematical model was developed to explain these differences, taking into account the chemical and physical interactions encountered in the reaction between the monomers (diisocyanate and dialcohol) for nanoconfined in AAO and bulk. In nanoconfinement, the polyaddition is catalyzed by hydroxyl groups on the pore wall, resulting in an increase in the rate of polymerization during the early stages of the reaction. At high conversions, the limited diffusion of the polymer chains results in a slower polymerization and a dispersity lower than that expected from bulk. Graphical abstract: Highlights: Step-growth polymerization within an AAO template was successfully performed. Reaction catalyzed by pore wall leading to rapid reaction times. Nanoconfinement of polymer chains leads to low dispersity polymer. Direct polymerization in AAO is faster and less energetic than polymer infiltration. Nanostructuration of the PU resulted in a superhydrophilic polymer.